Investigating the contextual interference effect using combination sports skills in open and closed skill environments - Cheong, J. P. G.; Lay, B.; Razman, R. (Journal of Sports Science & Medicine, 2016)
This study attempted to present conditions that were closer to the real-world setting of team sports. The primary purpose was to examine the effects of blocked, random and game-based training practice schedules on the learning of the field hockey trap, close dribble and push pass that were practiced in combination. The secondary purpose was to investigate the effects of predictability of the environment on the learning of field hockey sport skills according to different practice schedules. A game-based training protocol represented a form of random practice in an unstable environment and was compared against a blocked and a traditional random practice schedule. In general, all groups improved dribble and push accuracy performance during the acquisition phase when assessed in a closed environment. In the retention phase, there were no differences between the three groups. When assessed in an open skills environment, all groups improved their percentage of successful executions for trapping and passing execution, and improved total number of attempts and total number of successful executions for both dribbling and shooting execution. Between-group differences were detected for dribbling execution with the game-based group scoring a higher number of dribbling successes. The CI effect did not emerge when practicing and assessing multiple sport skills in a closed skill environment, even when the skills were practiced in combination. However, when skill assessment was conducted in a real-world situation, there appeared to be some support for the CI effect.